MANAJEMEN KURIKULUM DAN EVALUASI - Sukatin; Danny, Miftah Arbian Firhan; Huda, Rika Mustautinatul; Fajria, Zaiya Intan (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
This paper was made with several existing sources to find out what management and evaluation are. Curriculum management is a curriculum management system that is cooperative, comprehensive, systemic and systematic in order to realize the achievement of curriculum objectives. Evaluation or assessment is carried out in stages, continuously and openly. The results of curriculum evaluation can be used by educational policy holders and planners, and curriculum developers in selecting and establishing policies for developing the education system and developing the curriculum model used.